Efficacy and Safety of Levetiracetam vs. Phenobarbital for Neonatal Seizures: A Systematic Review and Meta-Analysis - Meng-Yuan Qiao (Frontiers Media S.A., 2021)
Background: Neonatal seizures are a common neurological emergency in newborns. Phenobarbital (PB) is the first-line antiepileptic drug (AED). However, PB has some side effects, such as hypotension and respiratory depression, and it can accelerate neuronal apoptosis in the immature brain. Levetiracetam (LEV), a new antiepileptic drug, has been used as a second-line drug for the treatment of neonatal seizures. Compared with PB, LEV has many advantages, including a low incidence of side effects and better neurodevelopmental outcomes. However, there are only a few systematic reviews of LEV for the treatment of neonatal seizures.Objective: To evaluate the efficacy and safety of LEV for neonatal seizures and to compare the efficacy, side effects, and neurological outcomes between LEV and PB in the treatment of neonatal seizures.Methods: The keywords LEV, PB, and neonatal seizure were searched in the MEDLINE, Cochrane Library, Web of Science, EMBASE, clinicaltrials.gov, and China National Knowledge Internet (CNKI) databases with a last update in July 2021 to collect high-quality studies. We collected studies studying the efficacy or safety of LEV and PB in the treatment of neonatal seizures applying strict inclusion and exclusion criteria. The data were extracted and outcome measures, including efficacy, side effect rate, neurological score, and mortality rate, were analyzed with RevMan 5.3 software.Results: Ten articles were finally included in the meta-analysis. The meta-analysis showed that there was no difference in efficacy between LEV and PB in the treatment of neonatal seizures. Compared with PB, the incidence of side effects of LEV was lower. The incidence of hypotension and respiratory depression in the LEV group was significantly lower than that in the PB group. In terms of long-term neurodevelopmental outcomes, there was no significant difference in the Bayley Scales of Infant Development (BSID) scores between LEV and PB.Conclusion: PB is still the first-line AED recommended by the WHO for the treatment of neonatal seizures. The new AEDs LEV may not have better efficacy than PB. At the same time, LEV is associated with better neurodevelopment outcomes and a lower risk of adverse effects. In addition, continuous EEG monitoring should be used to diagnose neonatal seizures to evaluate the severity of the seizures, remission, and drug efficacy.Systematic Review Registration: PROSPERO, identifier: CRD42021279029.